2011
DOI: 10.4028/www.scientific.net/amr.223.505
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Generation Mechanisms Based on Process Feed-Back and Decomposition of Feed Marks

Abstract: This paper proposes a novel integrated approach to the prediction of surface generation mechanisms which takes into account both cutting process outputs and distortions of the individual feed marks in comparison to an ideal kinematical model. For this task, the recorded surface roughness profile was decomposed using special algorithms. The mechanisms of real surface generation considered include the plastic side flow and spring back effects, the cutting edge sharpness and its wear, and dynamic interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The emergence of such evidence from a profile lends a physically meaningful basis for the identification of individual tool marks. It is furthermore suggested that mechanisms investigated by Grzesik and Brol such as plastic flow, friction, and elastic recovery [3] may obfuscate the ends of tool marks in visual inspection, but not affect CDI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of such evidence from a profile lends a physically meaningful basis for the identification of individual tool marks. It is furthermore suggested that mechanisms investigated by Grzesik and Brol such as plastic flow, friction, and elastic recovery [3] may obfuscate the ends of tool marks in visual inspection, but not affect CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, theorists interested in modeling surface generation from machining may benefit from statistically validated identification of tool marks, and visual identification may be difficult in some cases. Grzesik and Brol decomposed feed marks to study the mechanisms of their generation [3]. Secondly, the identification of tool marks may be useful in quality control; Carroll et al explain that there is value in automatically distinguishing defects from the rest of a machined surface [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is the measurement of the magnetic profile along tread’s circumference. This is so-called (1D) measurement [ 21 ], and the result is a circumferential profile of vector B . The B vector can consist of many projections of B in dependence of sensor design.…”
Section: Methodsmentioning
confidence: 99%
“…Methodology for determining the cumulative effects of several factors was recently proposed by Grzesik and Brol (2011). As the first attempt, the improved predicted model for Ra parameter in oblique turning with straight cutting edge, considering both the minimum undeformed chip thickness (h min ) and relative displacements of the tool traces (cutting vibration) within the surface profile (D( )), can be expressed in the form of Eq.…”
Section: Theory Of Surface Formation In Oblique Turning With Straightmentioning
confidence: 99%